Cost of corrosion - Kamis, Azmi (Faculty of Chemical & Natural Resources Engineering, 1992)
Corrosion affects all materials-metal and non-metal. Annually, its costs society billion of dollars. It is not only financially damaging to the economies, but also wasting our limited natural resources, damaging the environment and causing a great deal of human suffering. The understanding of corrosion with correct engineering application could greatly reduce the damaging effects and cost of corrosion.